2015
DOI: 10.1167/iovs.15-16395
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial–Mesenchymal Transition (EMT)-Related Cytokines in the Aqueous Humor of Phakic and Pseudophakic Fuchs' Dystrophy Eyes

Abstract: Simultaneous elevation of TGF-β1, TGF-β2, and MCP-1 concentrations in FECDpsph eyes confirms that cataract surgery leads to long-term alterations of the intraocular microenvironment. Positive correlation of increased aqueous TGF-β1 and MCP-1 levels with CPTR3.5 in pseudophakic FECD eyes suggests that changed cytokine levels may be involved in corneal decompensation after cataract surgery. Unchanged aqueous humor levels of EMT-related proteins analyzed in phakic FECD patients indicate that there is no primary r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
27
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 39 publications
3
27
3
Order By: Relevance
“…Similar to Matthaei et al, 1 we observed a significant upregulation of MCP-1 in FECD psph compared with FECD ph (P < 0.05) and Control ph (P < 0.001; Fig.). In addition, we found MCP-1 to be significantly upregulated in Edema psph compared with FECD ph (P < 0.001) and Control ph (P < 0.001).…”
supporting
confidence: 90%
See 3 more Smart Citations
“…Similar to Matthaei et al, 1 we observed a significant upregulation of MCP-1 in FECD psph compared with FECD ph (P < 0.05) and Control ph (P < 0.001; Fig.). In addition, we found MCP-1 to be significantly upregulated in Edema psph compared with FECD ph (P < 0.001) and Control ph (P < 0.001).…”
supporting
confidence: 90%
“…In addition, there was a significant difference in TGF-b2 concentration between both phakic groups (P < 0.05) and between both pseudophakic groups (P < 0.05), respectively, with a higher concentration in patients with FECD. This suggests that TGFb2 is in fact specific for FECD within each category of phakic or pseudophakic eyes.Transforming growth factor b3 was below and TGF-b1 was above the detection limit in the study of Matthaei et al 1 In our study, it was the reverse. Therefore, we cannot comment on the findings for TGF-b1, but we can give new information on TGFb3.…”
contrasting
confidence: 50%
See 2 more Smart Citations
“…In recent years, elevated levels of cytokines in the AqH have been reported to be associated with pathogenesis in various ocular diseases, such as FECD, 35 glaucoma, 17,18,36 ocular surface diseases, 37 and graft rejection. 38,39 We reported an elevation of inflammatory cytokines in eyes with bullous keratopathy.…”
Section: Discussionmentioning
confidence: 99%